Appunti su un testimone poco noto della terza redazione del «comentum» di Pietro Alighieri (con uno specimen d’edizione) (Carte Romanze, 2020)
The 36 G 27 manuscript of the Library of the Accademia dei Lincei e Corsiniana of Rome (= Linc), which transmits part of the third draft of the Comentum of Pietro Alighieri to the Divine Comedy, has never been collated before with the most famous Ottoboniano 2867 and Cassinese 512, nor placed in the stemma codicum. The contribution aims to fill this gap, demonstrating that the text of Linc is rather close to that of the Cassinese, given also the presence of common errors that confirm the presence of an antigraph common to the two manuscripts. In the end, a specimen of diplomatic-interpretative edition is proposed (from the XXIV canto of Inferno), with the addition of two bands of apparatus (critical and sources).
Keywords: Italian Philology; Pietro Alighieri; Dante; Stemma codicum; Specimen of critical edition